Anxiety Levels among Tuberculosis Patients: A Descriptive Study - Sofiana, Liena; Oktaviani, Nadia; Oktaviana, Ardyawati Wira (Universitas Ahmad Dahlan, 2025)
Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis and transmitted through airborne droplets. Despite global control efforts, TB continues to pose a major health challenge and remains one of the most fatal diseases after HIV/AIDS. In the Special Region of Yogyakarta, the treatment success rate for TB in 2021 was lowest in Sleman District (86.4%). Among its 25 community health centers, Depok III Community Health Center reported the highest number of TB cases during that year. Beyond the physical symptoms, TB patients often face psychological problems, particularly anxiety, which can be influenced by demographic and treatment-related factors such as age, sex, education, income, treatment duration, and side effects of medication. This study employed a quantitative descriptive design to explore anxiety levels among TB patients undergoing treatment at Depok III Community Health Center, with participants recruited using total sampling. Findings revealed that nearly half of the respondents experienced moderate anxiety (46.7%), while 13.3% reported severe anxiety. In contrast, 30.0% of patients showed no signs of anxiety and were categorized as normal. The analysis further indicated that anxiety levels were associated with several patient characteristics, including gender, age, educational attainment, income, and length of treatment. These results underscore the importance of addressing not only the physical aspects of TB but also the psychological well-being of patients, suggesting that comprehensive management strategies are essential for improving treatment outcomes and quality of life.